The narrative properties of the 19th-century verse novel : - Bacskai-Atkari, Julia, (Hamburg University Press,, 2019)
This book investigates the narrative properties of the 19th-century verse novel. The genre grew out of Lord Byron’s Don Juan and established itself in various European literatures, with famous examples such as Pushkin’s Eugene Onegin. The proposed analysis is unique in the existing literature in defining the genre based on formal properties and in examining its exceptional, reflexive structure in detail. Apart from 19th-century texts, verse novels from contemporary literature are also includ-ed, and thus the connection between these two contexts is discussed for the first time extensively.
Keywords: Byron; Genre theory; Reflexivity; Romanticism; Narrative structure; Verse novel; Fiction